Microbiologic picture of microflora of female urogenital organs. - Dyudyun, A. D.; Polion, N. M. (Medicni Perspektivi, 2016)
In this report authors give a detailed analysis of microorganisms that can contaminate mucous membranes of female urogenital system in normal range and in the formation of certain dysbiotic position. The composition of microorganisms that colonize the mucous membrane of the urogenital tract depends on many exogenous and endogenous factors. The main microorganisms that provide colonizing resistance of vaginal biotop (VB) are lactobacilli and lactobacteria. The protective properties of lactobacillus are implemented by antagonistic activity and ability to produce lysozyme and hydrogen peroxide. L. acidophilus, L. spp.; Propionbacterium spp.; Fusobacterium spp.; Porphyromonas spp.; Prevotella spp.; S. epidermidis and S. Saprophyticus novobionrezistentni and Streptococcus spp. and others are of definite importance in supporting normobiots of mucous membranes of urogenital system of women. Decreasing number of lactobacilli and other microorganisms of normobiota leads to colonization of mucous membranes of the vagina with G.vaginalis, B.bivies, B.disiens, B.melaninigenius, Mobiluncus, E.coli, E.fecalis, S.epidermidis and development of clinical manifestation of VB. The authors show microscopic and bacteriological characteristics of microorganisms that form normal microbiota and pathological states. The development of basic subjects promotes increasing number of the known microorganisms, important in the development of VB.